Colorimetric sensing of chloride and fluoride by 2-quinonimine functionalized gold nanoparticles - Sadhana Kundu; Pradip Kar (Next Nanotechnology)
Chloride and fluoride are very reactive water contaminants that have adverse effects on animal health as well as their psychochemical processes. The sensing of these two anions in an aqueous medium is important for clinical diagnosis, environmental monitoring, and various industrial applications. In this report, the stable colloid of gold nanoparticles functionalized (AuNPs) with 2-quinonimine (2-QI) was successfully synthesized to be used in the colorimetric sensing application of chloride and fluoride ions in an aqueous medium. A decrease in intensity of the Surface Plasmon Absorption (SPR) band in UV–VIS spectra was observed for colloids of AuNPs functionalized with 2-QI upon a gradual increase in the concentration of chloride or fluoride ions with respect to the water dilution. Though the intensity of the SPR band was found to decrease in the pH range of 2–12, the best result was observed at pH 2. A linearity range was observed up to 0.04 mM concentration of both the analyte for 880 μM AuNPs with sensitivity of ∼18–20 mM−1 and a limit of detection of ∼8–8.5 μM. An immediate selective decolorization was observed by the naked eye for 0.5 mL of 160 μM AuNPs in a 0.5 mL aqueous chloride solution of 15 mM and fluoride solution of 17.5 mM. The responses were found to be selective over the other common cations, anions, or biomolecules tested. The proposed sensing mechanism was explained as the accumulation of AuNPs in micro-particles by destroying the stabilization of AuNPs through dipolar interaction with 2-QI.